1993
DOI: 10.1093/ajcn/58.3.369
|View full text |Cite
|
Sign up to set email alerts
|

Can diarrhea induced by lactulose be reduced by prolonged ingestion of lactulose?

Abstract: Twelve healthy volunteers were studied for two test periods, at the beginning of which they ingested a diarrheogenic load (60 g) of lactulose in 350 mL water with 10 g polyethylene glycol 4000 (PEG); the two periods were separated by a lactulose feeding period of 8 d, during which a nondiarrheogenic load (20 g) of lactulose was taken twice daily. The transit time and flow rates of water and lactulose in the distal ileum of four subjects were not different before and after the lactulose feeding period. In the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 22 publications
2
27
1
1
Order By: Relevance
“…By prefeeding the prebiotic inulin, diarrhoea caused by the application of lactulose could be relieved (131) . These findings are in agreement with observations of Flourie et al (133) , who showed that primarily offering adult human subjects a low dose of lactulose increases fermentation and moderates diarrhoea during a period following a high dose of lactulose consumption. It appears that pre-feeding represents a form of adaption of the colonic microbiota, since a dose of indigestible carbohydrate that can be completely fermented might increase the overall capacity for fermentation, partly by inducing the production of bacterial glucosidases (133) .…”
Section: Diarrhoea: Occurrence After Weaning In Human Infants and Pigsupporting
confidence: 94%
“…By prefeeding the prebiotic inulin, diarrhoea caused by the application of lactulose could be relieved (131) . These findings are in agreement with observations of Flourie et al (133) , who showed that primarily offering adult human subjects a low dose of lactulose increases fermentation and moderates diarrhoea during a period following a high dose of lactulose consumption. It appears that pre-feeding represents a form of adaption of the colonic microbiota, since a dose of indigestible carbohydrate that can be completely fermented might increase the overall capacity for fermentation, partly by inducing the production of bacterial glucosidases (133) .…”
Section: Diarrhoea: Occurrence After Weaning In Human Infants and Pigsupporting
confidence: 94%
“…Digestive tolerance of maltitol A Ruskone-Fourmestraux et al Prolonged ingestion of slowly absorbed sugars, such as lactose and lactulose, results in changes in the metabolic activity of the colonic flora, especially a fall in breath excretion of H 2 , which increases its ability to ferment the sugar (Florent et al, 1985;Flourié et al, 1993;Launiala, 1968;Perman et al, 1981). As a result, there is efficient fermentation of the chronically ingested unabsorbed sugar, and thus a reduction in its diarrhoeogenic effect (Rambaud & Flourié, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The capacity to ferment unabsorbable sugars, such as lactose and lactulose, and to reduce their laxative effects can, however, be increased by regular ingestion of these sugars, which results in changes in the metabolic activity of the colonic flora, especially a reduced excretion of hydrogen in the breath (H 2 ) (Florent et al, 1985;Flourié et al, 1993;Launiala, 1968;Perman et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Colonic bacterial glucosidases are known to be substrate inducible (Macfarlane et al, 1988) and increased fermentation in the colon may decrease or even suppress diarrhoea by removing the osmotic effect of malabsorbed carbohydrates (Rambaud and Flourié, 1994) as well as stimulation of colonic sodium and water transport by short-chain-fatty acids resulting from the fermentation process. Reduction in diarrhoea following chronic ingestion of lactulose in lactose maldigesters has also been observed (Flourié et al, 1993) and a significant reduction in breath hydrogen excretion, diarrhoea and flatus has been reported following consumption of lactose after adaptive feeding periods (Johnson et al, 1993;Hertzler and Savaiano, 1996).…”
Section: Discussionmentioning
confidence: 91%